Diagnosis and Treatment of Gastroesophageal Reflux Disease - Vaezi, Michael F. (Springer International Publishing : Imprint: Springer, 2016)
This volume presents the most recent developments in diagnosis and treatment of patients with gastroesophageal reflux disease (GERD) and those who continue to be refractory to conventional GERD therapies. The book delineates the role of newly developed endoscopic therapies in GERD and outlines the best candidates for surgical fundoplication. Topics as the risks associated with GERD, lifestyle modification in GERD, and the role of H2RA and proton pump inhibitor therapy in treating reflux disease are also explored. Written by authorities in the field, Diagnosis and Treatment of Gastroesophageal Reflux Disease is a concise yet comprehensive resource that is useful for primary care providers, gastroenterologists, pulmonologists, surgeons, and ENT specialists.